Ancient classical theatre from the digital humanities: a systematic review 2010–21 - Martínez Nieto, Roxana Beatriz (Digital Scholarship in the Humanities, 2024)
The aim of this article is to offer a systematic review of digital studies that provide new research perspectives on ancient classical theatre. The undeniable progress in the field of computational analysis in the service of traditional textual interpretation is helping to study in greater depth and to interpret in greater detail the classical linguistic corpora that have come down to us through the manuscript tradition. The new model of digital research is integrated not only in the field of information technologies, but also in the field of e-learning, where we can already observe the implementation of a new educational model. Based on the digital processing of data on Greco-Roman theatre, a systematic review is presented, following the methodological principles of the PRISMA statement [Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2009 (2020)].
Keywords: classical theatre; digital humanities; systematic review